2018
DOI: 10.17582/journal.aavs/2019/7.1.38.44
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and Chemical Parameters of Traditional Siahmazgi Cheese Produced in Zanjan Province, Iran

Abstract: T he traditional dairy products, especially cheese, have an important place in Iranian food culture. The amount of cheese production in the United States is 4.8 to 8.6 million tons in Western Europe (Ledenbach & Marshall, 2009). Traditional cheese has got great interest by consumer for its nutritional quality among other cheeses (Blažić et al., 2017) as a result because of the consumers demand for this type of product, it's necessary to provide hygiene certificate for them. Since the shelf-life spam for dairy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…The salt increased during process of making cheese, in traditional and pasteurized cheeses, which are caused by reducing solids content and increasing dry matter of cheese, the results were in line with the foundings of Mirza Alizadeh et al, [6], Farahani et al, [10], Mortazavi et al, [9], Cetinkaya and Soyutemiz [12], and Psoni [13].…”
Section: Evaluation Of Saltsupporting
confidence: 83%
See 4 more Smart Citations
“…The salt increased during process of making cheese, in traditional and pasteurized cheeses, which are caused by reducing solids content and increasing dry matter of cheese, the results were in line with the foundings of Mirza Alizadeh et al, [6], Farahani et al, [10], Mortazavi et al, [9], Cetinkaya and Soyutemiz [12], and Psoni [13].…”
Section: Evaluation Of Saltsupporting
confidence: 83%
“…In none of the samples of traditional and pasteurized Siahmazgi cheeses tested, Salmonella was found. Mirza Alizadeh et al, [6] in his survey mentioned that no salmonella was observed in traditional Siahmazgi samples. The findings of the current study were in line with the study conducted by Dimitrovska et al, [18] in the Republic of Macedonia and Loghmanifar et al, [14], in Iran.…”
Section: Survey Of Salmonella Changesmentioning
confidence: 97%
See 3 more Smart Citations